The moment of decision from the perspective of deliberate and emergent strategies (2017)
The purpose of this paper is to contribute to the understanding of moments of decision for strategies based on the concept of deliberate and emergent strategies and the cycle that exists between them. The use of a strategy workshop incorporating the “beer game”, is employed, which allows for the creation of a deliberate strategy, followed by an abrupt end to the game, causing disruption and subsequent failure of the plan. The moment of decision concept was determined from the perspective of deliberate and emergent strategies, where the moment of decision results from a disruption of the deliberate strategy. This leads to an agent to a decision space where an emergent strategy can be constructed that results in continued viability in a system and allows for decisions to be made. Looking towards the future, it is with applied research activities that are associated with specific situations within the organization that are highlighted. As the main contribution shows, a relationship was seen between the cycle of deliberate and emergent strategies and decision timing, broadening the understanding of the temporal aspect of decisions.